Biological basis of aggressive behavior - O. A. Makushkina; O. I. Gurina; V. A. Golenkova (Неврология, нейропсихиатрия, психосоматика)
The review analyzes the role of serotonergic, dopaminergic, noradrenergic, and glutamatergic systems and neuroendocrine mechanisms, neuropeptides, and inflammatory mediators in aggression manifestation. We discuss the inconsistency of modern concepts about the neurochemical nature of aggressive behavior and the urgency of determining biological markers of social danger. Finally, questions of psychopharmacotherapy of aggressive behavior are reviewed.